2010
DOI: 10.1590/s1415-43662010001100013
|View full text |Cite
|
Sign up to set email alerts
|

Mobilidade de solutos em colunas de solo com água residuária doméstica e de suinocultura

Abstract: RESUMOCom o objetivo de avaliar o fator de retardamento, coeficiente de dispersão-difusão e curva de efluente dos íons cálcio, magnésio, sódio e potássio das águas residuárias de origem doméstica tratada e de suinocultura, realizou-se um experimento em laboratório com colunas de solos Argissolo Vermelho Amarelo e Neossolo Regolítico. Com o auxílio de frascos de Mariotte cerca de dois volumes de poros de água destilada foram passados nas colunas; em seguida, interligou-se outro frasco contendo as águas residuár… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
16

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 11 publications
1
5
0
16
Order By: Relevance
“…Soil in the columns was prepared manually, assuming a mean bulk density of 1.5 g cm −3 found for this type of soil (Santos et al 2012;Kang et al 2011;Oliveira et al 2011;Santos et al 2010). The layer of 0-10 cm was gently set, because the soil when plowed is less dense.…”
Section: P-leaching Experiments With Soil Columnsmentioning
confidence: 99%
“…Soil in the columns was prepared manually, assuming a mean bulk density of 1.5 g cm −3 found for this type of soil (Santos et al 2012;Kang et al 2011;Oliveira et al 2011;Santos et al 2010). The layer of 0-10 cm was gently set, because the soil when plowed is less dense.…”
Section: P-leaching Experiments With Soil Columnsmentioning
confidence: 99%
“…In the northeastern parts of Brazil, solid cattle manure and goat manure are frequently used in doses ranging from 4 to 20 Mg ha −1 (Sabourin et al 2000;Silva and Menezes 2007;Galvão et al 2008; In memoriam of Ignacio Hernán Salcedo.…”
Section: Introductionmentioning
confidence: 99%
“…Araujo et al (2000) reinforced the idea that the application of this technique to study ion movement in soil contributes to a more rational fertigation use, including using elements with low mobility. Santos et al (2010b) found that the lower the solution advance speed in the soil column, the greater the contact time was between the ions and the soil colloids, providing greater opportunities for solute retention and causing an increase in the retardation factor. For potassium ions (K + ) (Fig.…”
Section: Resultsmentioning
confidence: 99%